‘WHO AM I?’ INTERROGATING MY IDENTITY AS ESP TEACHER: PERSONAL NARRATION - Rafika Rabba Farah (University of Muhammadiyah Malang, 2018)
The notion of English for Specific Purposes (ESP) program which integrates language and content at one go could be challenging for language teachers as their expertise is only on the language, not the content. Consequently, it affects ESP teachers’ identity. This study takes a deeper look on a teacher’s personal experience teaching ESP that contributes to ESP teacher’s identity construction. It is a qualitative research using narratives as the approach, written records are taken as the main data. In the study, there are three participants in the research; two are ESP teachers and another is the researcher herself as she also involved in the teaching ESP. The study has revealed that the identity construction of ESP teachers is mainly built through two dimensions: students-related challenge and institutional challenge. To deal with students, teachers are no more as the primary source to knowledge; meanwhile, it is highly possible that students have more understanding than the teachers. To deal with institutional challenge, developing general English curriculum into more specific purposes is demanding for teachers. In addition, teaching ESP for more than one major in a semester adds to its complexity.